TRENDS IN HUMAN CAPITAL FORMATION AND EVALUATION OF THE INTERCONNECTION OF SOCIO-DEMOGRAPHIC PROCESSES IN RURAL AREA: A CASE STUDY OF VOLYN REGION, UKRAINE - Tetiana SHMATKOVSKA; Mykola DZIAMULYCH; Antonina GORDIICHUK; Nataliia MOSTOVENKO; Natallia CHYZH; Tetiana KOROBCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
A comprehensive analysis is relevant for present realities for Volyn and Ukraine as a whole, the problem – the demographic situation in rural areas, including reducing the number of a rural population due to natural processes of reproduction. The features of the rural settlement network. Democratic reproduction processes for the rural population for 1989 – 2018, its regional features and patterns of the settlement are analyzed. Based on the study of this phenomenon, methods of studying the influence of various demographic factors on the dynamics of rural demographic reproduction have been proposed. The article proved that the demographic situation and the possible appearance of threats to demographic processes in the future depending on the formulation and implementation of effective population policies today. Found that targeted regulatory impact on the demographic situation should be based on a comprehensive understanding of the nature of demographic processes reproduction.